MEMAHAMI NILAI RELIGIUSITAS DALAM KEPEMIMPINAN ‘AHOK’ SEBAGAI BENTUK REGULASI DIRI - M. Imron Abadi* (Belajar Bahasa, 2016)
Values reflect a person's behavior in accordance with the norms and the rules t applied in religion. Religious interpreted as properties associated with religious values. Religiosity value refers to the values which guides human behavior to the right destination. Religiosities value is the concept of man's relationship to God, man to other man, and man to himself. Religiosity value cannot be separated from man behavior toward the truth and his behavior toward the rules of the religion. This study aims: (1) to understand the value of religiosity in ‘Ahok’ leadership, (2) to determine the form of self-regulation in the leadership of ‘Ahok’. This study uses a qualitative approach using content analysis. Sources of data in this study comprise any recorded data related to Ahok’s performance; those data include any printed or electronic transcriptions of the mass media.This study examined the value of religiosity of ‘Ahok’ concerning with (1) the religiosity relationship of 'Ahok' to his God, (2) the religiosity relationship 'Ahok'  to the community, and (3) the religiosity relationship 'Ahok' to himself. In addition, the form of ‘Ahok’ leadership regulation comparises (1) receiving, (2) evaluating, (3) searching, (4) formulating, (5) implementing, and (6) assessing.Key words: Values, Religiosity, Leadership, Self-Regulation.